Delay characteristics of time-sensitive services in 5G networks - Jianyu CAO; Wei FENG; Ning GE (物联网学报)
For industrial applications, the time-sensitive services (TSS) and non TSS need to share the radio resources and the same buffer queue in 5G radio access network (RAN).This incurs the complex coupling and uncertainty of the delays.Considering the scenario where ON-OFF TSS and non TSS coexist, the calculation methods for the random delay (including queueing delay) characteristics were established based on the two-stage tandem queueing model, to obtain the mean value, standard deviation, bound violation probability and probability distribution of the delay of TSS.On this basis, the influence of non TSS on the random delay characteristics of TSS was analyzed.It is shown that the influence of non TSS on the random delay characteristics of ON-OFF TSS is related to the rotation frequency of ON-OFF stages.Moreover, the delay probability distribution of ON-OFF TSS has approximately the same right tail length as Gamma distribution.